Sea‐Ice Detection From Near‐Nadir Ku‐Band Echoes From CFOSAT/SWIM Scatterometer. Issue 6 (3rd June 2022) - Peureux, Charles; Longépé, Nicolas; Mouche, Alexis; Tison, Céline; Tourain, Cédric; Lachiver, Jean‐Michel; Hauser, Danièle
Abstract: SWIM on board CFOSAT is the first spaceborne, low incidence, rotating scatterometer, aiming at measuring in near‐real time ocean waves spectra. With five off‐nadir beams at incidences between 2° and 10° plus one nadir beam, it covers the Earth in 13 days, including polar regions thanks to its polar orbit. This work aims at exploiting SWIM data over ice regions with two objectives. An off‐nadir data‐based sea‐ice flag is here proposed that allows, first, to eliminate sea‐ice polluted echoes for improving the wave spectrum retrieval, and second, to open perspectives for application of sea‐ice monitoring with near‐nadir Ku‐band active sensors. To this end, the signature of both open water and sea‐ice radar backscatter is parameterized into Geophysical Model Functions. Then, comparisons with observed profiles through a Bayesian scheme provide a probability of sea‐ice presence. After comparison with both model (ECMWF‐IFS) and radiometer (SSMI) derived reference data sets, the proposed flag is found to be ready for operational use. At latitudes greater than 40° in absolute value, the proposed flagging algorithm exhibits accuracies of approximately 98% for all beams compared to SSMI data. Beam to beam performances are characterized and show potential for the characterization of sea‐ice at Ku‐band. Key Points: For the first time, sea‐ice is detected globally from Ku‐band off‐nadir up to 11° incidence thanks to the SWIM/CFOSAT data sets Fully analytical Geophysical Model Functions are derived for the Normalized Radar Cross‐Section over open water and sea‐ice A comparison of this new sea‐ice flag with SSMI ice concentration shows a high accuracy of our algorithm